Simplified modified Rankin Scale questionnaire correlates with stroke severity. (August 2013) - Bruno, Askiel; Close, Brian; Switzer, Jeffrey A; Hess, David C; Gross, Hartmut; Nichols, Fenwick T; Akinwuntan, Abiodun E
Objective: To further validate the simplified modified Rankin Scale questionnaire (smRSq), we compare it here to a well-established predictor of functional outcome after stroke, the initial stroke severity. Design: Retrospective correlation analysis. Participants: Forty patients identified from a registry of stroke patients treated with intravenous tissue plasminogen activator. Setting: Community and 17 hospital Emergency Departments within a web-based telestroke network throughout the state of Georgia, USA. Measures: Five certified raters assessed the initial stroke severities with the National Institutes of Health Stroke Scale (NIHSS) via the telestroke system. Over a 20 month period, one certified rater, unaware of the NIHSS scores, attempted to contact each patient in the registry to assess their functional outcomes with the smRSq via telephone. We analyzed patients who had the smRSq assessment at least three months after stroke. Results: Forty of 120 registered patients were contacted and qualified for this study. The baseline clinical characteristics of the 40 analyzed and the 80 disqualified patients were similar. The correlation between the initial NIHSS and the smRSq was good (r = 0.69, R 2 = 0.47, P < 0.001). Conclusions: The good correlation of the smRSq with the initial stroke severity further confirms the smRSq validity in assessing functional outcome after stroke.